Vegetable Salad as a Healthy Food Alternative: Organoleptic Test Method - Haezer Lisanias; Yunus Daniel Anus Laukapitang; Charles Tessy (Sekolah Tinggi Teologi Levinus Rumaseb Sentani, Papua, 2023)
Vegetables have health benefits. Tomatoes, carrots, lettuce, corn, cucumbers and mayonnaise as flavourings provide a taste that respondents like. The number of respondents is 22 students. The method used is a simple organoleptic test and the product SWOT test. Products are presented and evaluated. The results showed that the vegetable salad was well received in terms of taste, aroma, presentation. Overall, vegetable salad products can be used as an alternative to healthy food.